Business Law / An Introduction - Lopez D. Victor (Irwin Mcgraw-Hill, 1993)
The Legal Environment of Business, Sources of the Law and the Court System, Tort Law, Criminal Law, Contracts, Contracts: Offer and Acceptance, Contracts: Consideration, Contracts: Genuine Assent, Contracts: Legality, Contracts: Statute of Frauds, Contracts: Third-Party Beneficiaries and Assignment of Contracts, Contracts: Discharge and Remedies for Breach, Contracts for the Sale of Goods and Commercial Paper, Formation and Modification of the Sale Contract, Performance of the Sales Contract and Risk of Loss, Remedies for Breach of the Sales Contract and Warranties, Commercial Paper, Property, Personal Property and Bailments, Real Property, Wills and Trusts and Insurance, Business Organization, Agency and Employment Law, Partnerships, Corporations, Computerized Legal Research Using LEXIS, Glossary, Index.